A novel UWB reconfigurable filtering antenna design with triple band-notched characteristics by using u-shaped coppers - I.D. Saiful Bahri; Z. Zakaria; N. A. Shairi; N. Edward (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper proposed an UWB antenna with triple reconfigurable notch filters. By presenting there U-shaped coppers in the design, the potential triple interference in UWB applications can be rejected. Six PIN diodes are putted on the coppers to represent the OFF and ON tunable status in order to add reconfigurable characteristics to the UWB antenna. By using this ON and OFF tunable method, the current distribution of the proposed design changes and enables the antenna to have eight operation modes. The results prove that the proposed design can operate over the entire UWB frequency range (3.1 GHz to 10.6 GHz) and can filter out the target signals from the WLAN upper band (5.725 to 5.825 GHz), WLAN lower band (5.15 to 5.35 GHz) and X band frequency system (7.9 to 8.4 GHz) in one of the tunable configurations.